2022
DOI: 10.1101/2022.11.06.515311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative single-cell characterization of hypothalamus sex-differential and obesity-associated genes and regulatory elements

Abstract: Over 500 noncoding genomic loci are associated with obesity. The majority of these loci reside near genes that are expressed in the hypothalamus in specific neuronal subpopulations that regulate food intake, hindering the ability to identify and functionally characterize them. Here, we carried out integrative single-cell analysis (RNA/ATAC-seq) on both mouse and human male and female hypothalamus to characterize genes and regulatory elements in specific cell subpopulations. Utilizing both transcriptome and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 131 publications
1
0
0
Order By: Relevance
“…These results may however not accurately reflect regulation of FAIM2 expression in vivo as this gene is primarily expressed in the brain; furthermore, this miRNA product is a passenger strand that is typically found in lower abundance due to degradation after its complementary guide miRNA is loaded into an Argonaute protein during miRNA processing 68 . More recently, others carrying out global analyses have implicated an enhancer in the region harboring rs7132908 with a luciferase reporter assay and found that, in mouse neuronal hypothalamus cells, the obesity risk A allele significantly decreased enhancer activity with a minimal promoter 69 , consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These results may however not accurately reflect regulation of FAIM2 expression in vivo as this gene is primarily expressed in the brain; furthermore, this miRNA product is a passenger strand that is typically found in lower abundance due to degradation after its complementary guide miRNA is loaded into an Argonaute protein during miRNA processing 68 . More recently, others carrying out global analyses have implicated an enhancer in the region harboring rs7132908 with a luciferase reporter assay and found that, in mouse neuronal hypothalamus cells, the obesity risk A allele significantly decreased enhancer activity with a minimal promoter 69 , consistent with our results.…”
Section: Discussionsupporting
confidence: 91%